Young People and Media Making: Engaging Secondary School Students in Critical Media Literacy - Shanti Balraj, Mohammed Zin Nordin & N.V. Prasad (Wacana Seni Journal of Arts Discourse, 2007)
The media have a pervasive presence n young people's social and cultural experiences. Many young people's lives today are dominated by media where an average chilcl grows up with television, DVD player, radio, CD players, video games, mobile phones, computers and iPods (Livingstone 2002, Osgerby 2004). The texts and images produced by these media technologies help shape their views of the world. They contribute to educating young people about meanings, norms, values, practices, social relations and patterns of interaction (Buckingham 2002; Buckingham 1998; Buckingham 1995: Felitzen and Carlsson 2000). The meanings, messages and images generated by the media influence their everyday lives, specifically in the personal, schooling, working and the public spheres. The media shape our perceptions and ideas and inform daily decision-making. Gerbner (1999) notes that the media tell stories that animate our cultural environment and reveal how things in socieltes work, illuminating important and invisible relationships and hidden dynamics in life. These stories carry information and values about family, friendship, love, peace, weddings, education and so on. Furthermore, these stories present practices. behaviours and life-styles that are deemed as desirable or undesirable and actions that bring rewards or penalties (Budd, Craig and Steinman 1999).